Sublethal effects of a deltamethrin on feeding and defecation patterns of Triatoma infestans - Fernández, Nahuel (2022)
Triatoma infestans is the main vector of the Chagas disease in the Southern Cone of America. One of the main forms of transmission is the vectorial one, through infected feces of hematophagous insects of the Triatominae subfamily. The main way to reduce the incidence of the disease is the chemical control of the insect vector with pyrethroids in homes and peridomiciles. The complexity in the construction and materials of peridomiciliary structures prevent a uniform application of insecticides while leaving them exposed to environmental degradation. Thus, the surviving insects that live there will be exposed for a time to sublethal doses of the applied insecticide. Sublethal doses can have different effects on the biology of the insects. The objective of this work was to evaluate the effect of sublethal doses of deltamethrin on feeding and excretion/defecation patterns of T. infestans.